Phylogenetic, expression and functional characterizations of the maize NLP transcription factor family reveal a role in nitrate assimilation and signaling. Issue 3 (17th July 2018) - Wang, Zhangkui; Zhang, Lei; Sun, Ci; Gu, Riliang; Mi, Guohua; Yuan, Lixing
Abstract : Although nitrate represents an important nitrogen (N) source for maize, a major crop of dryland areas, the molecular mechanisms of nitrate uptake and assimilation remain poorly understood. Here, we identified nine maize NIN‐like protein ( ZmNLP ) genes and analyzed the function of one member, ZmNLP3.1, in nitrate nutrition and signaling. The NLP family genes were clustered into three clades in a phylogenic tree. Comparative genomic analysis showed that most ZmNLP genes had collinear relationships to the corresponding NLP s in rice, and that the expansion of the ZmNLP family resulted from segmental duplications in the maize genome. Quantitative PCR analysis revealed the expression of ZmNLP2.1, ZmNLP2.2, ZmNLP3.1, ZmNLP3.2, ZmNLP3.3 and ZmNLP3.4 was induced by nitrate in maize roots. The function of ZmNLP3.1 was investigated by overexpressing it in the Arabidopsis nlp7‐1 mutant, which is defective in the AtNLP7 gene for nitrate signaling and assimilation. Ectopic expression of ZmNLP3.1 restored the N ‐deficient phenotypes of nlp7‐1 under nitrate‐replete conditions in terms of shoot biomass, root morphology and nitrate assimilation. Furthermore, the nitrate induction of NRT2.1, NIA1, and NiR1 gene expression was recovered in the 35S::ZmNLP3.1/nlp7‐1 transgenic lines, indicating that ZmNLP3.1 plays essential roles in nitrate signaling. Taken together, these results suggest that ZmNLP3.1 plays an essential role in regulating nitrate signaling and assimilation processes, and represents a valuable candidate for developing transgenic maize cultivars with high N‐use efficiency.